Dental Therapy of Patients Prior to Endoprostheses: A Retrospective, Telephone-Based Cohort Study - Gerhard Schmalz; Julian Wirtz; Rainer Haak; Fabian Fenske; Andreas Roth; Dirk Ziebolz (MDPI AG, 2023)
The aim of this study was to assess, whether patients prior to endoprosthesis (EP) visit their dentist for need-oriented therapy and whether this would be associated with the occurrence of complications. Based on a cohort of patients, which was orally investigated prior to EP surgery between 04/2020 and 12/2021, a telephone interview was performed at least six months after EP implantation. Patients were classified into either low-risk (LR), moderate-risk (MR), or high-risk (HR) groups. Participants were interviewed based on a structured questionnaire regarding dental visits, dental therapy, and potential complications during the observational period. Out of the 311 patients from the baseline cohort, 96 patients after EP implantation could be included (participation rate of 31%). Nineteen patients were in LR (20%), 41 in MR (43%), and 36 in the HR group (37%). Overall, 79% (n = 76) of the patients followed the recommendation to visit their dentist; 94% of patients within the HR group visited the dentist (p = 0.02). Dental treatment procedures included tooth cleaning (57%), periodontal treatment (31%), restorative therapy/filling (28%), and tooth extraction (28%). In 64% of the HR patients (n = 23), the potential oral foci with a risk of EP infection were eliminated by their general dentist. Fourteen different complications occurred within the observation period, without any group effect (p > 0.05). In conclusion, most patients prior to EP visit their general dentist following referral, especially if they have a potential oral focus. The effect of dental clearance on infectious complications of EP remains unclear, whereby further clinical studies are needed.